2022
DOI: 10.1111/codi.16332
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and patient reported symptoms after colorectal cancer in a Swedish population

Abstract: The number of colorectal cancer (CRC) survivors is increasing in Sweden due to a rise in CRC incidence and improved survival, related to advances in treatment [1]. The benefit in oncological outcome can be at the cost of treatment-related adverse effects on functional outcomes and negative impact on quality of life (QoL) [2][3][4]. Bowel problems are very frequent after treatment for CRC. Low anterior resection syndrome (LARS) is common after colorectal anastomosis and consists of one or more of urgency, leaka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Other studies with patients treated for colorectal cancer have shown significantly lower QoL for those who received ostomies 8,14 . A cancer diagnosis in itself can lower the QoL 31 …”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Other studies with patients treated for colorectal cancer have shown significantly lower QoL for those who received ostomies 8,14 . A cancer diagnosis in itself can lower the QoL 31 …”
Section: Discussionmentioning
confidence: 94%
“…8,14 A cancer diagnosis in itself can lower the QoL. 31 In a study from 2022, patients who had their ostomies for a long time had better QoL than those with newly-created ostomies. 32 Surprisingly, slightly better QoL was found in EthioTemp than in EthioPerm, although they used home-made stoma bags.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Therefore, we compared QOL and stool function between the two groups of patients. The EORTC QLQ-C30 scale is widely used to assess the QOL of patients with cancer [ 26 , 27 ]. To the best of our knowledge, this is the first study involving the QOL and anal function in patients with R-NETs measuring 1–2 cm.…”
Section: Discussionmentioning
confidence: 99%
“…One of the impacts is the disruption of many aspects of life, including emotional, psychological, and spiritual activities (Majda et al, 2022); Therefore, it is very important to focus on a spiritually fulfilling ministry. Assistance from the physical aspect has been carried out through curative efforts to reduce symptoms, especially pain experienced by patients, but has not improved the patient's quality of life because psychological pressure is also experienced by patients, especially at the beginning of diagnosis (Sjövall et al, 2023). Patients with advanced malignant tumors of the digestive tract cannot be treated or are unrestable, so they require palliative therapy to improve their quality of life.…”
Section: Introductionmentioning
confidence: 99%